KURIKULUM PENDIDIKAN AGAMA ISLAM PADA RAUDHATUL ATHFAL DIAN AL-MASTIYAH - Iyoh Mastiyah (Badan Litbang dan Diklat Kementerian Agama RI, 2014)
Islamic Education curriculum used by Raudhatul Athfal (Islamic Kindergarten) Dian Al-Mastiyah is thematic curriculum. It is designed as an integral, holistic and everyday-life-oriented as well as studentcentered. By using the thematic curriculum, learning experiences in Raudhatul Athfal (RA) Dian Al Mastiyah become more complete and more meaningful. This study tries to explain about the thematic Islamic education curriculum.